Assessment of quality performance measures for primary percutaneous coronary intervention: A report from a tertiary referral centre in Switzerland. Issue 6 (October 2016) - Haas, Céline; Fournier, Stephane; Iglesias, Juan-Fernando; Trana, Catalina; Roguelov, Christan; Locca, Didier; Lauriers, Nathalie; Muller, Olivier; Eeckhout, Eric
Aims: The present study aimed to document a local pattern of care in consecutive patients undergoing primary percutaneous coronary intervention for ST-elevation myocardial infarction (STEMI) in a tertiary centre in Switzerland. Methods: A retrospective study was conducted at the University Hospital of Lausanne, Switzerland. A total of 389 consecutive patients undergoing primary percutaneous coronary intervention for STEMI between 2009 and 2010 were studied. The audit focused on 14 items derived from the American College of Cardiology/American Heart Association 2008 quality performance measures position paper on STEMI management. These indicators all corresponded to a class 1 recommendation at the time of the study period. Results: All patients received aspirin and anticoagulation within 24 hours after admission. Only 31.3% of patients received beta-blocking agents within 24 hours of admission. Left ventricular function was evaluated in 89.2% of cases and referral for cardiac rehabilitation was achieved in 78.5% of eligible patients. Patients subsequently transferred to another facility for further inpatient care had significantly less evaluation of left ventricular function (82.0% vs. 97.5%, P <0.0001). Global adherence to all performance measures was significantly higher among younger patients (45.9% vs. 31.4%, P <0.0075). Conclusions: The present study, which provides a snapshot on quality performance between 2009 and 2010 in a referral centre for primary percutaneous coronary intervention, demonstrates a suboptimal application of the global guidelines on STEMI management. This observation is mainly driven by a low prescription of beta-blocking agents, a class IA indication at that time. This observation should be put in perspective to current practice.